PENGARUH DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN DIMEDIASI OLEH WORD OF MOUTH PADA PRODUK SKINCARE NEWFIVEZ - idiljan, Desri komala sari; Nuriya Santi, Ira; Zahara, Zakiyah; Tambaru, Rachman (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
This study aims to determine the effect of Digital Marketing on purchasing decisions for Newfivez skincare products in Palu City which is mediated by Word of Mouth. This study uses a quantitative approach with a survey method through distributing questionnaires to 100 Newfivez consumers. Data analysis was carried out using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) with the help of SmartPLS 4.1 software. The results showed that Digital Marketing has a positive and significant effect on Word of Mouth, and Word of Mouth has a significant effect on purchasing decisions. In addition, Word of Mouth is proven to mediate the relationship between Digital Marketing and purchasing decisions. These findings suggest that proper implementation of Digital Marketing can drive purchasing decisions indirectly through increasing Word of Mouth among consumers.